2023
DOI: 10.1002/app.54399
|View full text |Cite
|
Sign up to set email alerts
|

Smart elastomer sanitizer with chemically bonded active compound and on‐demand‐release antimicrobial functionalities

Abstract: Hand or surface sanitizers are all liquid‐based products which can be mainly categorized as alcohol or non‐alcohol based. The constant release of highly persistent disinfectants and chemicals is hazardous to the environment and human health. Herein, a new concept of solid elastomer sanitizer with inherent fast‐killing antimicrobial property is described. Silicone (PDMS) was chosen as the elastomer where the active antimicrobial component of imidazolium polymer (PIM) was carefully modified and incorporated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…PU-Zn@MOF materials were evaluated for their durability by “accelerated aging” and “surface wipe” tests . Accelerated aging test results indicated that the PU-Zn@MOF materials had excellent durability (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PU-Zn@MOF materials were evaluated for their durability by “accelerated aging” and “surface wipe” tests . Accelerated aging test results indicated that the PU-Zn@MOF materials had excellent durability (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…PU-Zn@MOF materials were evaluated for their durability by "accelerated aging" 39 and "surface wipe" tests. 40 Accelerated aging test results indicated that the PU-Zn@MOF materials had excellent durability (Figure 5a). The antimicrobial efficacies against E. coli and S. aureus were maintained at >6 log reduction following 2 months of aging treatment (equivalent to 2 years of shelf life under normal conditions).…”
Section: Table 3 Antimicrobial Efficacy Of Zn@mof Against Clinically ...mentioning
confidence: 99%